STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI DIGITAL GURU MELALUI PENGGUNAAN MEDIA INTERACTIVE FLAT PANEL (IFP) STUDI KASUS DI SDN MARGAASIH CIKANCUNG DAN SDN CILULUK 2 CIKANCUNG - Supyan Sauri; Susi Susanti; Neneng Purwanti; Asep Fauzi Amanu (STKIP Subang, 2025)
The rapid development of digital technology requires teachers to continuously improve their digital competence, supported by effective school leadership strategies through the use of technology-based learning media such as Interactive Flat Panels (IFP). This study aims to analyse the strategies employed by principals to enhance teachers’ digital competence through the use of IFP at SDN Margaasih Cikancung and SDN Ciluluk 2 Cikancung. A qualitative approach with a case study method was applied, using interviews, observations, and documentation for data collection. The theoretical framework is based on educational leadership, teachers’ digital competence, and the POAC management approach (planning, organising, actuating, and controlling). The findings indicate that principals implement systematic strategies through programme planning, resource organisation, training and mentoring activities, as well as continuous monitoring of IFP use in teaching practices. In conclusion, POAC-based principal strategies are effective in improving teachers’ digital competence.